Clinico-Radiological and Pathological Correlation of Breast Lesions in Patients Presenting to a Tertiary Hospital in Western Nepal - Sharma, Prakash; Shrestha, Elina; Tiwari, Prabhat Kumar (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Breast masses are frequently encountered problem, especially in females. Mammography and ultrasound are considered the standard imaging techniques for detection and evaluation of breast disease. The study was done to discuss the role of mammography and ultrasound in evaluation of breast mases with cytological correlation and to compare the sensitivity, specificity, positive predictive value and negative predictive value of ultrasonography6 with mammography in breast masses in different age groups and in patients with different breast density. MATERIALS AND METHODS: It was a non randomized prospective study carried out in Manipal teaching hospital Pokhara. The data for study was collected from patients with breast lump who attended the department of Radiology during the period from October 2013 to October 2014. Mammography and ultrasonography were performed on all cases presented with breast lump. A Fine needle aspiration cytology correlation was then performed with formed the basis for definitive judgement. RESULTS: The study analyzed 50 total numbers of patients presented to Radiology department who had breast lumps. Patients were aged between 20 and 75 years. Maximum numbe3r of patients were between 40 and 49 yrs constituting 40%. The mean age was 39.8 years ± 12.85 yrs. Ultrasound was significantly more sensitive than mammography in age less than 40 years. Mammogram had a significantly higher sensitivity than ultrasound in age group of more than 40 yrs. By using combined modalities (ultrasonography combined with mammogram), all benign cases were diagnosed correctly. For malignant breast masses, 10% were diagnosed as false negative but no cases were diagnosed false positive by combined modalities. Ultrasound was more sensitive than mammography in dense and heterogeneously dense breast whereas mammography was more sensitive than ultrasound in predominantly fatty breast. CONCLUSION: Combination of ultrasound and mammogram is more sensitive than other modality alone. Journal of Universal College of Medical Sciences, Vol. 5, No. 2, 2017, Page: 40-44